The Cytotoxicity Effect of Extracted Pigment from Haloarcula sp. on MDA-MB-468 Breast Cancer Cell Line - Saghar Shahbazi; Mohsen Zargar; Mohammad Reza Zolfaghari; Mohammad Ali Amoozegar (Iranian South Medical Journal, 2022)
Background: Halophilic microorganisms have the potential to produce new biomolecules, including anti-cancer compounds, for medical applications. The purpose of this study was to evaluate the anti-cancer properties of pigments extracted from native Iranian halophilic Archaeon. Materials and Methods: Pigment extract of Haloarcula sp. previously isolated and identified from Aran-Bidgol Lake was extracted. The effect of the extracted pigment on MDA-MB-468 breast cancer cell line was tested by MTT method and PI and FITC staining. Cells with different concentrations of pigment extract were incubated for 24, 48 and 72 hours. Finally, the expression of apoptotic genes, including BAX, CASP3, CASP7, CASP9, P21, P53, and SOX2, was examined by Real-Time PCR. Statistical analyses of the data were performed using the t-test and Repeated-Measures ANOVA. Results: Compared to untreated cells, the pigment extract inhibited the viability of MDA-MB-468 cells significantly after 48 hours at a concentration of 45.95 μg/ml (p*<0.05). In addition, the total population of early and late apoptotic cells (44.4%) increased in the studied cell line, which was associated with a significant enhancement of the expression of the P53, BAX, CASP7, and CASP9 genes. Conclusion: Halophilic archaea can be considered a suitable source of natural pigments with anti-cancer activity and potential benefits in chemotherapy.